The perils of returning to school: New insights into the seasonality of youth suicides - Vincent Chandler; Dörte Heger; Christiane Wuckel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
Taking advantage of temporal and geographical variations in the timing of school holidays in Germany, this paper finds that school holidays cause an 19 percent (0.03 percentage points) decrease in the probability of youth suicide. This effect is constant across different types of holidays (fall, Christmas, winter, Easter, Pentecost, and summer). Moreover, we find evidence of a spike in suicide propensity in the first two days following the end of school holidays. The results are robust to the inclusion of a series of control variables and to different definitions of youth. Overall, this paper suggests that school holidays have a beneficial impact on the well-being of students and that suicide prevention efforts are particularly important in the days following the end of holidays. – – Die Studie nutzt die zeitliche und geographische Variation in deutschen Schulferien, um die Wirkung von Schulferien auf die Selbstmordrate von Schülerinnen und Schülern in Deutschland zu untersuchen. Die Analyse stellt fest, dass Wahrscheinlichkeit eines Suizids unter Jugendlichen in den Ferien um 19 Prozent sinkt. Dieser Effekt ist konstant über verschiedene Arten von Ferien (Herbst, Weihnachten, Winter, Ostern, Pfingsten und Sommer). Darüber hinaus zeigt sich, dass die Wahrscheinlichkeit für einen Suizid in den ersten beiden Tagen nach dem Ende der Schulferien besonders hoch ist. Diese Ergebnisse sind robust für eine Reihe von Kontrollvariablen und unter verschiedenen Definitionen von Jugendlichen. Insgesamt legt die Analyse nahe, dass die Schulferien einen positiven Einfluss auf das Wohlbefinden der Schüler haben und dass Suizidpräventionsbemühungen in den Tagen nach dem Ende der Ferien besonders wichtig sind.
Keywords: I12; I21; 330; school; suicide; teenagers; bullying; stress